Mesh-Assisted Laser-Induced Plasma Spectroscopy Using Pulse Carbon Dioxide Laser for Analysis of Powder Material by Confining the Powder in a Hole and Employing a Condensation Technique - Ali Khumaeni; Asep Yoyo Wardaya; Heri Sugito; Nasrullah Idris; Kiichiro Kagawa (Universitas Gadjah Mada, 2019)
Analysis of impurity in powder samples has been made by using metal-assisted laser-induced plasma spectroscopy utilizing a pulsed CO2 laser. Various powders including food powder, supplement powder, baby powder, and medicine powder were employed as sample materials. Experimentally, the powder sample was tightly put in a hole made on a metal plate and a metal mesh was placed on the powder surface. A pulse CO2 laser (10.6 μm, 1500 mJ) was irradiated on the powder surface passing through the metal mesh. Luminous plasma was induced by mesh just above the mesh when a part of laser energy attacked the mesh. The other part of laser energy impinged the powders and ablated fine particles of powder to the plasma to be atomized and excited. Identification and analysis of elements in powder were successfully conducted. A linear calibration curve of Cu in baby powder has been demonstrated with an intercept zero, certifying that the present technique was a high possibility to be employed for semi-quantitative analysis of elements in powder material. It was proved that by applying the present technique and employing a condensation technique, the detection sensitivity of Cr impurity in the powder sample increased about twenty times compared to the case without condensation. The limit of detection of Cr in rice powder sample was 25 mg/kg. The proposed method was very convenient for the identification and analysis of elements in the powder sample.